2002
DOI: 10.1038/sj.sc.3101269
|View full text |Cite
|
Sign up to set email alerts
|

Pain classification following spinal cord injury: The utility of verbal descriptors

Abstract: Objectives: To determine the predictive utility of verbal descriptors to distinguish between pain types following spinal cord injury (SCI). Design: Cross-sectional. Setting: USA. Methods: Participants (n=29) completed the Short Form ± McGill Pain Questionnaire (SF-MPQ) for each pain site reported. A total of 64 pain sites were reported with 80% of the sample reporting multiple pain sites. Each pain site was categorized using three di erent SCI pain classi®cation schemes. The predictive utility of verbal descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 41 publications
3
43
0
3
Order By: Relevance
“…9 'Aching' was chosen by one-third of participants. Aching' may describe musculoskeletal pain, 9,22 but was found by Cardenas 10 to describe both musculoskeletal and SCI pain (defined as neurologic pain below the lesion level in an area without normal sensation). 'Tingling' has been considered a descriptor for neuropathic pain 9,10,22 and was not a common choice in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 'Aching' was chosen by one-third of participants. Aching' may describe musculoskeletal pain, 9,22 but was found by Cardenas 10 to describe both musculoskeletal and SCI pain (defined as neurologic pain below the lesion level in an area without normal sensation). 'Tingling' has been considered a descriptor for neuropathic pain 9,10,22 and was not a common choice in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These words may describe or relate to trauma or inflammation to various structures within the shoulder joint or the capsule as they may describe pain of musculoskeletal origin. 9,18,19,22 Pain in the upper trapezius region was described as 'sharp', 'pinching', 'pulling', 'hot' and 'tender'. Descriptors of heat may refer to neuropathic pain referred from the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of at-level SCI pain is suggested by characteristics such as: 4,5,9,16,20,21 Sensory deficits within the pain distribution Allodynia or hyperalgesia within the pain distribution Endorsement of one or more of the following pain descriptors: 'hot-burning' , 'tingling' , 'pricking' , 'pins and needles' , 'sharp' , 'shooting' , 'squeezing' , 'painful cold' and 'electric shock-like' Pain occurring in a segmental pattern as described above, which is thought to be due to syringomyelia, should be classified as at-level SCI pain or, more specifically (using tier 3 entries), at-level SCI pain due to/associated with syringomyelia. Note that the current NLI often is higher than the original NLI in patients who develop syringomyelia following a SCI.…”
Section: Nociceptive Pain Typesmentioning
confidence: 99%
“…Neuropathic pain that occurs in this distribution and that cannot be attributed to the spinal cord damage should be classified as other (neuropathic) pain. The presence of below-level SCI pain is suggested by characteristics such as: 4,5,9,16,[20][21][22] Sensory deficits within the pain distribution Allodynia or hyperalgesia within the pain distribution (for persons with incomplete injury) Endorsement of one or more of the following pain descriptors: 'hot-burning' , 'tingling' , 'pricking' , 'pins and needles' , 'sharp' , 'shooting' , 'squeezing' , 'painful cold' and 'electric shock-like' Below-level SCI pain can occur in persons with complete injuries and in those with incomplete injuries. Neuropathic pain associated with cauda equina damage is radicular in nature, and therefore defined as at-level SCI (neuropathic) pain, regardless of distribution.…”
Section: Nociceptive Pain Typesmentioning
confidence: 99%
“…However, a recent study has investigated the use of pain descriptors when classifying SCI pain and concluded that verbal descriptors alone are not su cient for pain classi®cation. 25 In non-SCI populations, women often report more numerous pain locations than men 17,19 and more severe pain. 18 This was not the case in our study, where no di erences were found.…”
Section: Discussionmentioning
confidence: 99%